Associations between type 2 diabetes mellitus and chronic liver diseases: evidence from a Mendelian randomization study in Europeans and East Asians - Zhao, Yue; Li, Di; Shi, Hanyu; Liu, Wei; Qiao, Jiaojiao; Wang, Shanfu; Geng, Yiwei; Liu, Ruiying; Han, Feng; Li, Jia; Li, Wei; Wu, Fengyun (Frontiers in Endocrinology, 2024)
Multiple observational studies have demonstrated an association between type 2 diabetes mellitus (T2DM) and chronic liver diseases (CLDs). However, the causality of T2DM on CLDs remained unknown in various ethnic groups. Methods: We obtained instrumental variables for T2DM and conducted a two-sample mendelian randomization (MR) study to examine the causal effect on nonalcoholic fatty liver disease (NAFLD), hepatocellular carcinoma (HCC), viral hepatitis, hepatitis B virus (HBV) infection, and hepatitis C virus (HCV) infection risk in Europeans and East Asians. The primary analysis utilised the inverse variance weighting (IVW) technique to evaluate the causal relationship between T2DM and CLDs. In addition, we conducted a series of rigorous analyses to bolster the reliability of our MR results. Results: In Europeans, we found that genetic liability to T2DM has been linked with increased risk of NAFLD (IVW: